GAM MODEL AND TOURIST VALORIZATION OF GEOSITES PLOČNIK - Stanković, Miroslav; Milovanović, Stefan (Bulletin of Natural Sciences Research, 2017)
In Serbia, there are several sites from the Neolithic period, but there is only one site from the period of existence of the Vinča-Tordoš family (5500-4800 BC). In this paper, we will try to become familiar with the site named Pločnik by using two methods. This site is one of many archeological sites in Serbia, but it stands out uniquely because it is under state protection. The methods to be applied are GAM model and tourist valorization.
Keywords: Vinča-Tordoš; Pločnik; Neolithic; tourist valorization; GAM model; Archaeological site